Association between asymmetric dimethylarginine and sarcopenia in community-dwelling older women - Miyuki Yokoro; Naoto Otaki; Megumu Yano; Tomomi Imamura; Norikazu Tanino; Keisuke Fukuo (Scientific Reports, 2023)
Abstract Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of endothelium nitric oxide synthesis and causes endothelial dysfunction that may be related to sarcopenia. However, the association between ADMA and sarcopenia has not been studied. We evaluated the correlations between plasma ADMA levels and sarcopenia in community-dwelling older women. In total, 144 community-dwelling older women participated in this study. Plasma ADMA levels were measured using a competitive enzyme-linked immunosorbent assay. Skeletal muscle mass, measured in terms of bioimpedance and grip strength, was used to assess sarcopenia. Plasma ADMA levels were significantly higher in participants with sarcopenia than in those without sarcopenia. Through receiver-operating characteristic curve analysis, the cutoff value of plasma ADMA level for sarcopenia was estimated at 0.57 μM. Sarcopenia was significantly more prevalent in participants with higher plasma ADMA levels than in those with lower plasma ADMA levels. According to logistic regression analysis, the crude odds ratio of higher plasma ADMA levels in participants with sarcopenia was 4.57 (95% confidence interval, 1.82–11.47; p = 0.001). Reductions in the skeletal muscle mass index over 2 years were significantly greater in participants with higher plasma ADMA levels. In conclusion, plasma ADMA levels were significantly associated with sarcopenia in community-dwelling older women.